Ekhakhamela - Machi, Nolwazi Fortunate (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2019)
My collection of isiZulu poems is based on my rural and traditional upbringing. It draws on language and customs which have shaped and defined me as a woman born in the South of KwaZulu-Natal. I write about how I have to conform to both a rural life and an urban one that forms my second world. I find myself having to switch between these lives, which benefits me a lot, and I feel a responsibility to bring hope to young people especially from the rural side, that nothing is wrong with being who and where they are. My writing is influenced by authors such as Nazim Hikmet, Mafika Gwala, and Mazisi Kunene who encourages black writers to write about their own customs and stories rather than embracing 'western civilization' and foreign languages. I also like the contemporary subjects and the humour in Dr Nakanjani Sibiya's work.
Keywords: Xhosa poetry